Common Fixed Point Theorems on Tricomplex Valued Metric Space. (30th May 2022) - Mani, Gunaseelan; Gnanaprakasam, Arul Joseph; Haq, Absar Ul; Baloch, Imran Abbas; Jarad, Fahd
Abstract : In this paper, we introduce the notion of tricomplex valued metric space and prove some common fixed point theorems. The presented results generalize and expand some of the literature well-known results. We also explore some applications of our key results.